Outbreaks of Foodborne Illness Associated with Melons - Clara Diekman; Matthew D. Krug; Ashley T. Myers; Rachel McEgan; Keith R. Schneider; Michelle D. Danyluk (EDIS, 2021)
In recent years, foodborne illness outbreaks have become more prevalently associated with produce. Melons (specifically cantaloupe, honeydew, and watermelon) are popular commodities consumed around the world. Despite the manner in which they are prepared, melons are commonly consumed raw without a processing step which would eliminate pathogenic bacteria. This 10-page major revision was written by C. Diekman, M. D. Krug, A. T. Myers, R. McEgan, K. R. Schneider, and M. D. Danyluk. https://edis.ifas.ufl.edu/fs258